Enhancing Science Impact in the Coastal Zone through Adaptive Learning - Smith, T.; Carter, W.; Thomsen, D.; Mayes, G.; Nursey-Bray, M.; Whisson, Glen; Jones, Roy; Dovers, S.; O'Toole, K. (Coastal Education and Research Foundation, 2009)
The impact of science to support coastal management may be reduced through social and institutional barriers. Some of these barriers include ineffective community engagement, lack of interaction between scientists and decision makers, and institutional decision-making tradition related to hierarchical mandates. A three-year project has commenced to examine the role of adaptive learning in overcoming some of these barriers to maximize pathways for science and improve decisions made in the coastal zone. Adaptive learning is one of five project areas targeted to enhance science impact, being undertaken by a consortium of nine Australian universities funded through the CSIRO Collaboration Fund. Two of the strategies being explored to maximize adaptive learning to improve science impact include: (i) development of an on-line toolkit for embedding adaptive learning within coastal organizations; and (ii) development and testing of monitoring and evaluation frameworks to improve adaptive learning interventions. While focused on an Australian context, the project addresses broad issues of social and institutional barriers that have relevance for many coastal scientists and decision makers around the globe.